Development of a Creative Economy Based on Local Wisdom in Empowering MSME economic improvement to Face the Modern Market from a Sharia Economic Perspective - Sofian Syaiful Rizal; Devi Akmalia (Enrichment : Journal of Management, 2022)
This study aims to better understand the existence of the creative economy as a strategy that is predicted to be able to trigger competitiveness both on a national and international scale to face the modern market. Until now, unemployment, poverty, and massive exploitation of nature, which ultimately causes inequality in terms of social and economic growth, are still classic problems that require solutions. Therefore, there is a need for harmony in obtaining these solutions, one of which is economic harmonization and local wisdom, which of course can trigger economic competitiveness and increase productivity which in turn improves people's living standards while maintaining culture, and customs that become the distinctive character that viewed from the perspective of Islamic economics. This study uses a descriptive-qualitative approach with data collection methods of observation, interviews, and data analysis. As a sample, the researchers took the reality of the development of a Creative Economy Based on Local Wisdom in empowering the economic improvement of MSMEs to Face the Modern Market with a Sharia Economic Perspective Study at PT Paiton Energy (Paiton Energy) and PT Paiton Operation & Maintenance Indonesia (POMI). The results of the analysis state that the empowerment of MSME economic improvement has a multiplier effect on the community because this product has contributed to moving the service trade sector and MSMEs. As well as being able to restore the values ​​of local wisdom of the community both in terms of integration of the economic sector and integration of the social sector which includes ukhuwah Islamiyah, and the creation of social solidarity